Khazanah Pendidikan Islam Berbasis Kearifan Lokal: Analisis Nilai dalam Tradisi Manjau-Maju Perkawinan Adat Lampung Saibatin - Firnando Firnando; Cahirul Anwar; Imam Syafe'i (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
Indonesia is rich in local wisdom, this wealth is a value that is the basis for someone to act. Local wisdom also forms the philosophical basis of education. On that basis, this study aims to analyze the value of Islamic education in the tradition of manjau-maju Lampung Saibatin custom. This study used a qualitative method, which was carried out by establishing an intense relationship with informants in the activities of the Lampung Saibatin traditional manjau-forward tradition in the village of Suka Negeri Jaya. The findings obtained from this study are: first, the Manjau-maju tradition is still being preserved by the Suka Negeri Jaya village community without conflicting with Islamic teachings, and in this tradition it involves a lot of young people in every implementation, this is certainly good for educating the younger generation to love Lampung traditional culture and preserving it, secondly, contained Islamic educational values ​​such as worship values, moral values, and also creed values, which are manifested through the implementation procession, prayers offered, no media that leads to polytheism, deliberation values, hospitality, please help, respect leadership. Therefore the researchers recommend an increase in literacy and books about Lampung customs so that the younger generation can better understand the culture that exists in Indonesia.